Geology and Landslide Vulnerability Zoning Using Analytical Hierarchy Process in The Kebanaran Area and Surrounding Areas, Mandiraja District, Banjarnegara Regency, Central Java - Indra Permana Jati; Weldina Ayu Tri Novita; Januar Aziz Zaenurrohman (Engineering Faculty, UNSOED, 2025)
The Kabanaran area and its surroundings, Mandiraja District, Banjarnegara Regency, Central Java is an area located on the banks of the Serayu River and borders the southern mountain range. The research area is also an area that allows landslides to occur, this is due to several natural factors and human activity factors that cause landslides. This research was conducted to explain the relationship between geological conditions and landslide vulnerability factors in the research area. The method used is the Analytical Hierarchy Process (AHP) method. This method matches several parameters that are considered as factors in the occurrence of landslides and is given a value based on the weighting criteria. Based on the results of the study, there are several parameters, such as natural factors, geology, and other activities that affect landslides in the research area, including rainfall intensity, lithology, assessment frequency and weighting as to obtain the final value in determining the landslide vulnerability zone. The results of these calculations produce 4 levels of landslides, namely low landslide vulnerability zones, moderate landslide vulnerability zones, high landslide vulnerability zones, and very high landslide vulnerability zones.